Definition of a platform worker in the context of the definition of paid worker under the rules on the coordination of social security systems - Kasprowski, Szymon; Kiełbowicz-Dziwulska, Agnieszka (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
The aim of this article is to analyse the definition of a platform worker introduced under the EU Directive in connection with the provisions on the coordination of social security systems. In particular, attention is paid to the issue of the link existing on the grounds of the coordination of social security systems to the definition of a paid worker. The effects of the introducing a definition of platform work will also have implications in the context of social security law, hence it is reasonable to perform an analysis of EU law in the area of coordination of social security systems. The study also refers to the provisions of Polish law with regard to social security and the basis of work provision. The development of digital platforms is a significant socio-economic issue, therefore there is a need for regulations in the field of the protection of people performing work under such conditions. This is why measures are being taken, such as the introduction of the directive defining platform work, which is to be implemented by Member States in their legal systems. This makes it all more important to analyse the regulations on the coordination of social security systems, taking into account the Polish specificity, where the labour market is characterised by various forms of employment.